Pengaruh Literasi Keuangan, Gaya Hidup dan Tingkat Pendapatan Terhadap Pengelolaan Keuangan Mahasiswa Universitas Slamet Riyadi Surakarta - Fredina Putri Arumsasi; Rina Susanti (Teewan Journal Solutions, 2026)
This study aims to examine the significant influence of financial literacy, lifestyle, and income level on the financial management of students at Slamet Riyadi University Surakarta. Using a quantitative approach, this study utilises primary data collected from 100 students through proportional random sampling. The research instruments were validated and tested for reliability, followed by testing classical assumptions such as multicollinearity, autocorrelation, heteroscedasticity, and normality. Data analysis was conducted using multiple linear regression, as well as t-tests, F-tests, and the coefficient of determination (R²) to test hypotheses and evaluate model accuracy. The results of the validity and reliability tests showed that all variables of financial literacy, lifestyle, income level, and financial management were valid and reliable. After passing the classical assumption tests, the regression analysis results showed that the three independent variables (financial literacy, lifestyle, and income level) significantly influenced students' financial management. These findings are confirmed by the results of the t-test and F-test, which indicate that the regression model used is appropriate. However, the R² value of 34.9% indicates that these variables can only explain less than a third of the variation in students' financial management, while the remaining 65.1% is influenced by factors outside the scope of this study.